A Space for 'Thinking Differently': Learning and Teaching Practical Theology in Non-confessional Settings. Issue 2 (November 2015) - Stuerzenhofecker, Katja
Abstract : This article develops a context-specific approach to learning and teaching of Practical Theology in non-confessional settings in higher education. Where Practical Theology is not linked to ministerial training and exclusively Christian discipleship, the first task is to redefine its purpose for a diverse body of students and staff of all faiths and none. The classroom is conceived here as a space for 'thinking differently' in dialogue with alterity about contemporary issues in lived religion with the aim of shaping ethically engaged habitus . This is framed as the process of 'becoming divine' through self-transcendence and active contribution to this-worldly transformation. Underlying this approach is a theological anthropology of the human subject as fragment which is open to the future. The use of autoethnography is explored as a method for narrative identity formation which complements and is complemented by engagement with public debate. The non-confessional setting draws attention to fluid identities beyond the binary of 'church' and 'world', and to issues of pluralism in identity formation. Finally, questions arise regarding the role of the educator and the management of their own 'confession'.